Websites and portfolios of participants in new media art events: characteristics of artists and their productions - Mucciolo, Daniel Costa Vianna; Zanella, Andréa Vieira (DAT Journal, 2026)
This article presents documentary research developed with the aim of mapping and analyzing characteristics of artists who are currently working with new media arts. To this objective, websites of new media arts events and festivals were visited, of events happened between 2009 and 2019. Once the artists were identified, their portfolios and official websites were visited, between August 2021 and December 2022, totaling 1,792 electronic addresses. The analysis of these materials made it possible to identify some characteristics: the nationality of the participants, with Japan, USA and Austria being the most frequent; the prevalence of artists identified as male; the different forms of collaboration between artists; the different formats used; the presence of artists on social networks, among other topics. This research sought to bring an understanding of artists who use digital media and their ways of exposing themselves on the internet.